YAP/TAZ-associated cell signaling – at the crossroads of cancer and neurodevelopmental disorders - Aderonke O. Ajongbolo; Aderonke O. Ajongbolo; Sigrid A. Langhans (Frontiers in Cell and Developmental Biology)
YAP/TAZ (Yes-associated protein/paralog transcriptional co-activator with PDZ-binding domain) are transcriptional cofactors that are the key and major downstream effectors of the Hippo signaling pathway. Both are known to play a crucial role in defining cellular outcomes, including cell differentiation, cell proliferation, and apoptosis. Aside from the canonical Hippo signaling cascade with the key components MST1/2 (mammalian STE20-like kinase 1/2), SAV1 (Salvador homologue 1), MOB1A/B (Mps one binder kinase activator 1A/B) and LATS1/2 (large tumor suppressor kinase 1/2) upstream of YAP/TAZ, YAP/TAZ activation is also influenced by numerous other signaling pathways. Such non-canonical regulation of YAP/TAZ includes well-known growth factor signaling pathways such as the epidermal growth factor receptor (EGFR)/ErbB family, Notch, and Wnt signaling as well as cell-cell adhesion, cell-matrix interactions and mechanical cues from a cell’s microenvironment. This puts YAP/TAZ at the center of a complex signaling network capable of regulating developmental processes and tissue regeneration. On the other hand, dysregulation of YAP/TAZ signaling has been implicated in numerous diseases including various cancers and neurodevelopmental disorders. Indeed, in recent years, parallels between cancer development and neurodevelopmental disorders have become apparent with YAP/TAZ signaling being one of these pathways. This review discusses the role of YAP/TAZ in brain development, cancer and neurodevelopmental disorders with a special focus on the interconnection in the role of YAP/TAZ in these different conditions.